Kepemimpinan yang Kuat Dalam Manajemen Pendidikan Islam Perspektif Hadis - Dadan F. Ramdhan (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to reveal strong leadership in the management of Islamic education perfective hadith. This research uses qualitative research methods with a descriptive approach to literature studies. The results and discussion of this research show that the figure of a strong leader in an education management has a meaning, they are the ones who are able to be responsible, trustworthy and professional at work. This research concludes that strong leadership is a recommendation in Islamic teachings, even in the hadith it is said that a strong believer is better and more Allah loves than a weak believer, this study recommends that a leader should have and master the principles of carrying out management in an education. Keywords: Management; Leader; Hadith